DAMPAK PEMBEBASAN NARAPIDANA PADA LINGKUNGAN MASYARAKAT DI TENGAH WABAH VIRUS COVID-19 - Nurul Aulia Khoirunnisa (LP2M IAIN Tulungagung, 2020)
Abstract : Every person in Indonesia has human rights including the right to social security for his life as stipulated in article 28H paragraph (1) of the 1945 Constitution that everyone has the right to obtain human rights fairly including inmates. Indonesia is now hit by a covid-19 virus outbreak and is social distancing. As a result, there are considerations to free prisoners but follow the conditional free procedure set out in Ministerial Regulation and Human Rights No. 03 of 2018. The research objectives were to find out: (1) prisoner parole procedures; (2) justice for inmates; and (3) the impact of prisoners' prarole.